(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly transformed modern educational practices, creating new opportunities for enhancing students’ knowledge competence. The aim of this study is to develop and evaluate a methodological approach to improving students’ knowledge competence through the effective integration of artificial intelligence technologies in higher education.